(untitled) (Research, Society and Development, 2020)
The compound juices are increasingly sought after by the consumer due to the high nutritional and functional values added, and can be developed with a diverse range of regional foods. Thus, the objective was to evaluate the effects of different sweeteners in the preparation of drinks composed of cashew and whey, in order to provide a healthy and differentiated product in the food market. Six formulations of compound drinks were prepared, of which three were sweetened with the use of bee honey and three with commercial sugar, in different concentrations of whey and water. Drinks and raw materials were evaluated for physical-chemical parameters and beverages were evaluated sensorially for sensory acceptance and purchase intention. The data obtained were analyzed through the Analysis of Variance, in a completely randomized experimental design, comparing the averages by the Tukey test at a level of 5% of significance. The raw material used is within the standards required by current legislation, except for the whey pH. The physico-chemical constitution of honey added value to the formulations in which honey was used. The acceptance of the juices did not differ significantly and showed that the formulations were well accepted. The purchase intention of formulations A and B was superior, demonstrating that the developed drinks can be a viable alternative for the diversification of the food market.